Personal Carbon Trading in the United Kingdom: Considering opportunities in times of climate change and the financial market crisis - Franziska Teichmann (2020)
Personal Carbon Trading in the United Kingdom: Considering opportunities in times of climate change and the financial market crisis Executive Summary Global warming and climate change is the biggest challenge that nations will be facing worldwide in the next decades. Greenhouse gas emissions have been increasing sharply over the last hundred years and need to be reduced as soon as possible in order to reduce further warming and assure manageability of the current changes. The financial market crisis of the last years has shifted the focus of policy makers and governments away from environmental objectives and has affected economies of many countries. Governments now need to combine economic and ecologic objectives to secure economic recovery and necessary emission abatement targets. Personal carbon trading is one policy that might be able to combine both targets and secure the long term shift towards a low-carbon economy. The scheme has been developed and investigated over the last years in the United Kingdom and is a very attractive instrument. It includes domestic households in an economy wide emission trading scheme. Through placing a cap on all national emissions it ensures, theoretically, that any given abatement target can be achieved. Under the scheme each household receives a set allowance of carbon allowances on a per-capita basis which then need to be surrendered when buying electricity and fuel. If a household emits less than average it can sell the surplus allowances and will therefore financially gain from the scheme. Households emitting above average need to buy additional allowances at a market price. Since the domestic sector accounts in the UK for about 40% of all emissions, of the 100% allowances, only 40% are allocated to individuals. The other 60% are auctioned off to businesses, the public and voluntary sector, that similar to individuals need to surrender these permits when buying or producing energy or fuel. There are several different personal carbon trading schemes, namely TEQs, Cap and Share, PCAs and other, which differ in terms of scope, allocation and participation. The scheme which is the basis for this paper is the Tradable Energy Quotas (TEQs) scheme developed by David Fleming. As aforementioned, the scheme ensures with a national cap that any given abatement target is met via distributing the equivalent in carbon allowances. The nature of the scheme, with including domestic households actively, ensures an increase in public awareness towards climate change issues and in regards to their own emissions. Households will be able to earn extra money if reducing their carbon footprint and will loose financially if not. This scheme is therefore very likely to bring about some creative individual behaviour and participation in actively searching for ways to reduce emissions. The scheme is also very equitable since it distributes allowances on an equal per-capita basis. The only adjustments which would have to be made are regarding low-income households which would loose from the scheme because of insufficient funds to insulate their home or buy a low-fuel car. Several studies show that when educating individuals about the scheme and other emission reduction scheme like a tax or upstream trading, they tend to choose personal carbon trading. Taxation is the strongest substitute instrument to reduce emissions and is often preferred by policy makers due to its less progressive nature and virtually no administration efforts. On the other hand a tax instrument is harder to predict in terms of emission abatement and will not stimulate the behavioural changes that are anticipated from a personal carbon trading scheme. While a tax does not require a lot of beforehand administration and implementation costs, a personal carbon trading scheme does. One representative study from 2008 illustrates the initial set up costs to be very high, but will be offset after a few years due to high governmental revenues from the auctioning procedure of the carbon allowances to businesses. Running costs of TEQs scheme are also considerably higher than those of a tax instrument, but are again being amortized by the generated revenues. For further insight David Fleming, the inventor of the TEQs, and Michael Kopatz, a project leader at the Wuppertal institute for climate, environment and energy, were interviewed. While Mr. Kopatz is more in favour of achieving necessary emission reduction with the existing policy instruments, David Fleming is convinced that the TEQs scheme will be implemented in the future. This might become necessary because of peak oil or the impending climate change impacts. After the financial market crisis, the introduction of a personal carbon trading scheme will offer an economy an instrument towards more sustainability and a low-carbon future. The initial scheme costs will be offset by the generated revenues and public acceptance is likely to be more in favour of it than other proposed emission reduction instruments. The scheme may also help an economy through stimulating research and production on renewable energies and green technologies, creating jobs and securing national welfare on a long term basis that might in jeopardy when fossil fuel scarcity arrives. The scheme has so far been discussed in the British House of Commons, after being backed by the Environmental Audit Committee. The House of Commons eventually concluded that work on the scheme would be winded down, but the Environmental Audit Committee remains in favour of the scheme.